Reframing Festivals: From Celebration and Tourism to Cornerstones of the Creative Industries - CUDNY, Waldemar (Journal of Environmental Management and Tourism, 2025)
Festivals have emerged as multifaceted phenomena that not only drive cultural consumption and stimulate tourism but also function as creative hubs integral to the growth of the creative industries. This conceptual study synthesizes existing literature and real-world examples to examine the interconnections between festivals, tourism, and the creative industries, positioning festivals as essential contributors to the creative economy. Rooted in the cultural and creative sectors, festivals attract travelers and serve as platforms for artistic innovation, knowledge exchange, and the formation of temporary creative clusters. They contribute to socio-economic development, urban transformation, and place branding, while strengthening the activities and networks of the creative class. The article highlights the dual role of festivals in both cultural consumption - through performative culture and tourism - and creative production, emphasizing their capacity to foster education and innovation. It further proposes a conceptual framework that captures the dynamic interplay between festivals and the creative industries, addressing existing gaps in institutional recognition and academic discourse.